Antibiotic Susceptibility Pattern of Pseudomonas aeruginosa and Detection of Virulence Genes in a Tertiary Care Hospital, Kathmandu, Nepal - Ojha, Tek Raj; Sah, Anil Kumar; Karn, Govind Lal; Parajuli, Pramila (Nepal Medical College Journal, 2024)
Pseudomonas aeruginosa is one of the most common causes of hospital-acquired infections. It threatens worldwide public health because of its intrinsic antibiotic resistance and virulence. In this context, this research aimed to determine the occurrence of P. aeruginosa in a clinical setting, examine its susceptibility to antibiotics, and detect the presence of virulence genes, viz. exoY, oprL and toxA in all isolates. It was a cross-sectional study carried out from June 2022 to December 2022. A total of 1356 clinical specimens were collected and processed in the laboratory for Gram staining, culture techniques, and biochemical tests. The Kirby-Bauer disk diffusion method was applied to examine the antibiotic susceptibility pattern and conventional PCR was used to detect the virulence genes in all confirmed P. aeruginosa isolates. 40.5% of specimens showed bacterial growth, of which only 3.02% were identified as P. aeruginosa. Among them, 61.0% were multidrug resistant and 29.2% were β-lactamase producers. Aztreonam (70.7%) was the most effective antibiotic. Among all P. aeruginosa isolates, 68.3% isolates were exoY positive, 61.0% were oprL positive and 56.1% were toxA positive. Strategic interventions are required to stop the emergence and spread of antimicrobial resistance as a result of the isolation of multidrug resistant (MDR) isolates carrying these virulence genes. This study can benefit the medical staff and the entire community in building a surveillance system and enhancing infection control procedures.